CYTOKINES AND ITS MAIN ROLE IN BACTERIAL VAGINOSIS IN PREGNANT WOMEN (Modern American Journal of Medical and Health Sciences, 2025)
Cytokines are a universal regulatory system of mediators that control the processes of proliferation and differentiation of cellular elements in the hematopoietic, immune and other homeostatic systems of the body. Violation of regulatory mechanisms is a condition for the development of pathological conditions and diseases, and in these cases, cytokines play the role of pathogenetic factors. Cytokines produced by T-helpers type 1 (Th1) are the most important inducers of the cellular immune response, hematopoiesis and reparative processes. Cytokines produced by T-helpers type 2 (Th2) promote the activation of B-cells and the production of antibodies, i.e. they activate the humoral immune response. Th2 cytokines participate in the development of allergic reactions and have an anti-inflammatory effect. Deficiency of Th1 cytokines in combination with high level of Th2 cytokines is a sign of immunosuppression and anergy of immune response. In some cases, the criterion of dysregulation of the immune system is precisely the imbalance of cytokines of opposing pools, and not the level of hypercytokinemia of a single mediator. To determine the imbalance, it is important to evaluate the ratio of interferon γ (IFNγ)/interleukin-10 (IL-10) – the leading cytokines in their groups.